Prevalence and determinants of hypertension and diabetes mellitus in an urban area of Coimbatore - Jayaraj, Naveen Prabhu; Shanmugam, Jeevithan; Duraisamy, Shanmugapriya; Padmavathy, Loganathan (International Journal Of Community Medicine And Public Health, 2020)
Background: Owing to change in behavior and lifestyle patterns, diabetes mellitus and hypertension are in increasing trend worldwide. They are associated with various complications resulting in high morbidity. Early detection of these would necessitate the prevention of complications associated with it and improves the quality of life of the people. The objective of the study was to assess the prevalence and determinants of diabetes mellitus and hypertension among urban population in the field practice area of a tertiary care hospital in Coimbatore. Methods: 299 individuals of both sexes belonging to six wards in the field practice area of a tertiary care hospital in Coimbatore were randomly selected and screened for diabetes mellitus and hypertension. Diagnosis was based on American Diabetic Association and JNC 7 guidelines for diabetes mellitus and hypertension respectively. Data on various factors associated was collected using pretested validated semi structured questionnaire. Results: Overall prevalence of diabetes mellitus and hypertension was found to be 32.44% and 38.8% respectively with newly diagnosed diabetes mellitus and hypertension of 4.02% and 7.37%. Overall adherence was found to be 80%. Factors such as elderly age, sedentary life style, non-vegetarian diet, obesity are found to be associated with both diabetes mellitus and hypertension. Conclusions: Almost one in every third person found to be having either diabetes mellitus/hypertension or both with 20% non-adherence to treatment. This high prevalence necessitates the need for adoption of various strategies to combat the risk factors and to promote healthy life style.